Winter condition variability decreases the economic sustainability of reindeer husbandry - Pekkarinen, Antti-Juhani; Rasmus, Sirpa; Kumpula, Jouko; Tahvonen, Olli (Ecological Applications, 2023)
Wild and semidomesticated reindeer are one of the key species in Arctic and subarctic areas, and their population dynamics are closely tied to winter conditions. Difficult snow conditions have been found to decrease the calving success and survivability of reindeer, but the economic effects of variation in winter conditions on reindeer husbandry have not been studied. In this study, we combine state-of-the-art economic-ecological modeling with the analysis of annual reindeer management reports from Finland. These contain local knowledge of herding communities. We quantify the occurrence probabilities of different types of winters from annual management reports and analyze the effects of this variation in winter conditions on reindeer husbandry using an age- and sex-structured bioeconomic reindeer-lichen model. Our results show that difficult winters decrease the net revenues of reindeer husbandry. However, they also protect lichen pastures from grazing, thereby increasing future net revenues. Nonetheless, our solutions show that the variability of winter conditions overall decrease the net income of herders compared to constant winter conditions. Low lichen biomass appears to make reindeer management more sensitive to the effects of difficult winter conditions. We also found that it is economically sensible to use supplementary feeding during difficult winters, but the net revenues still decrease compared to average winters because of the high feeding costs. Overall, our analysis suggests that the increasing variability of winter conditions due to climate change will decrease net revenues in reindeer husbandry. This decrease will still occur even if the most extreme effects of climate change do not occur. This study shows that combining a state-of-the-art bioeconomic model and practitioner knowledge can bring compatible insights, ideas, results, and a bottom-up perspective to the discussion. Peer reviewed